Role of polar anticyclones and mid-latitude cyclones for Arctic summertime sea-ice melting - Wernli, Heini; id_orcid:0 000-0001-9674-4837; Papritz, Lukas (Nature Geoscience, 2018)
ISSN:1752-0908 ISSN:1752-0894